A Comparative Analysis of Dissolution Profiles of Furosemide Tablets Available in the Argentinean Market (Part 2) - Han, Yong K.; Simionato, Laura D.; Calvo, Romina G.; Mattei, María B.; Segall, Adriana I. (Current Advances in Chemistry and Biochemistry Vol. 9, 2021)
The rate and the extent of drug dissolution and its absorption depend on the characteristics of the active pharmaceutical ingredient (API) as well as the dosage form properties. In this work dissolution profiles of furosemide tablets of nine commercial products marketed in Argentine were evaluated. All Brands fulfill the specifications of dissolution test of USP. Comparison of dissolution profiles were carried out by model-dependent and model independent approaches. The Weibull model provided the best kinetic curve adjustment. Brands IV, VI and IX had the best fitting, with the maximum determination coefficient and the smallest AIC values. Results obtained via model-independent approach show that there was not significative difference in Dissolution efficiency between the reference product and Brands II, III and IV and in Mean dissolution time between the reference product and Brands II, III, IV and V. Using fit factors, only Brands I and III were similar. It has been demonstrated in vivo bioequivalence of furosemide market products interchangeability with generics should be avoided.